Surveillance of adverse drug reactions and drug–drug interactions with pediatric oncology patients in a south Indian tertiary care hospital. (July 2020) - Joseph, Bency; Scott, Julius X; Rajanandh, M G
Objective: The present study was conducted to evaluate the pattern of occurrence of adverse drug reactions and drug–drug interaction in a pediatric oncology unit of a tertiary care hospital. Methods: A prospective, observational study was conducted in the Department of Pediatric Oncology, Sri Ramachandra Medical College and Hospital, India. Patients were monitored actively for the occurrences of any adverse drug reaction during the study period. Patient's demographic details, clinical, and treatment data were collected for drug–drug interaction analysis. The detected adverse drug reaction was assessed for causality, severity, and preventability. Drug–drug interaction identified was rated based on their level of urgency and the nature of actions necessary to respond to an interaction. Results: Of 176 patients, 118 were detected for the occurrence of various adverse drug reaction. The majority of the cases were suffering with acute lymphocytic leukemia (67.9%). Vincristine was noted for a maximum number of adverse drug reaction in cytotoxic drugs. Rash is the most frequently occurred reaction. Assessment of causality showed that the majority of cases are "probable" (60.16%). In evaluating the severity of adverse drug reactions, 57.6% reactions were moderately severe and 74.5% of the reactions were preventable. Upon assessing the drug–drug interaction, 38.13% of the prescription needs to be monitored and 10 drug–drug interactions were under the risk category of "X." The majority of the adverse drug reaction was moderately severe in nature and those were preventable. Conclusion: Since pediatrics are vulnerable population, they must have a thorough surveillance system for adverse drug reaction and drug–drug interaction; thereby, a positive impact on the medication-use system and improved patient care can be achieved.